Perception of Workplace Discrimination among Immigrants and Native Born New Zealanders - Bridget M. Daldy; Jacques Poot; Matthew Roskruge (Institute for the Study of Labor (IZA), 2013)
Despite considerable research on differences in labour market outcomes between native born New Zealanders and immigrants, the extent of discrimination experienced by the foreign born in the workplace remains relatively unexplored. We use micro data from the Confidentialised Unit Record File of the 2008 New Zealand General Social Survey (n = 8,721) to examine the determinants of self-reported discrimination in the workplace. We find that immigrants are significantly more likely than New Zealand-born employees to report that they experience discrimination in the workplace. There are noticeable gender differences in determinants of perceived discrimination, which interact with birthplace. The highest likelihood of self-reported workplace discrimination is found amongst migrants from Asia and the Pacific Islands. Discrimination is more likely to be reported by those with higher education and those who are mid-career. We test and correct for selection bias in measuring the impact of factors influencing perceived discrimination and find such bias to be present for men but not for women.
Keywords: F22; J01; J71; 330; immigration; workplace discrimination; New Zealand; sample selection bias